A Study on the Effects of Urbanization in China: Optimizing Weather Research and Forecast Models – Chemistry - ZHANG JINYUE , ZHANG JINYUE; DR. YASMIN CHE ANI , DR. YASMIN CHE ANI; DR. NORAISYAH TAJUDIN, DR. NORAISYAH TAJUDIN (International Journal of Multidisciplinary Research and Studies, 2024)
Direct, "This research looks at how land use change affects pollution concentrations in two rapidly developing areas of China: the Yangtze River Delta and the Jing-Jin-Ji (Beijing-Tianjin-Hebei) region, using both direct and indirect feedback. Predictions of air quality in rapidly developing areas require more recent land use data. The US Geological Survey's (USGS) Advanced Very High-Resolution Radiometer (AVHRR) data from April 1992 to March 1993 at 1 km spatial resolution is used as the default land use data collection in WRF-Chem (Loveland et al., 2000). This study modifies WRF-Chem to allow for the updating of land use data sets, and the method is demonstrated with data from the Moderate Resolution Imaging Spectroradiometer (MODIS) in the mid-2000s. The US Geological Survey (USGS) and NASA's Terra and Aqua satellites (MODIS) land-cover maps are used to analyze land-use data in order to "simulations of the atmospheric and chemical fields in these two regions during the 1990s and investigate the influence of urbanization.